Assessing sustainable development of a historic district using an ecological footprint model: a case study of Nanluoguxiang in Beijing, China. Issue 1 (4th October 2016) - Dai, Linlin; Xu, Bixia; Wu, Bihu
Abstract : Historic districts constitute a major part of urban space and serve as essential carriers of urban historical and cultural heritage. Quantitative assessment for the sustainable development capacity of a historic district is an important part of research on sustainable urban development. In the present study, we modified the existing ecological footprint (EF) model by using component analysis and considering the main features of a historic district. The EF model of historic districts was constructed in two dimensions: residents and tourists. A case study was performed in Nanluoguxiang in Beijing, China, to estimate the total EF and ecological carrying capacity (EC). The results showed that the EF was substantially higher than the EC, whereas the EF of tourists was higher than the EF of residents in Nanluoguxiang. Finally, we analysed the structural composition of the EF and proposed an effective way for implementing sustainable development in historic districts by EF reduction. We also put forward strategies for the targeted control of ecological needs and EF reduction from the perspectives of residents and tourists.